In silico analysis of enzyme involved in enrichment of citronella oil. (1st January 2011) - Sahu, Divya; Kumar, Ashutosh; Pandey, D.M.
Citronella oil is one of the essential oils obtained from Cymbopogon sp. having medicinally important aromatic chemicals (like citronellal, citronellol, hydroxy-citronellol and geraniol) exhibiting insecticidal, anti-oxidant and anti-inflammatory effects. Geraniol Dehydrogenase (GDH) is responsible for the degradation of Citronella oil. Therefore, we aimed to generate 3D structure of GDH and a potent specific GDH inhibitor by homology modelling, virtual screening of ligand database and molecular docking. Inhibitor model indicated strong binding affinity to the binding pocket of GDH and varying affinity for different ligands. Obtained structures will open the possibility of testing new inhibitor families, in addition to new substituent for the already known lead structures.